NUTRIENT PROFILE OF POND SOILS IN TRIPURA AND IMPACT OF SOIL ACIDITY ON POND SOIL PRODUCTIVITY - DATTA, M. K.; SAHA, RATAN K.; PRAKASH, CHANDRA (Journal of the Inland Fisheries Society of India, 2021)
The heterogeneity in soils, characteristics in north eastern (NE) region, is due to the interacting effects of various factors such as climate, topography, vegetation and living organisms (Dasgupta, 1980, Sharma et al., 2006).